Corporate Governance in Pre-university Education International Experiences: Lessons Learned - Tlaia, Mohamed Elsaied Mohamed (The Arab Journal of Administration, 2025)
The Research Dealt With The Role of The Principles of Governance in Pre-University Education Institutions, and a Review of a Conceptual Framework for Institutional Governance, its Principles and Determinants, and the global variables that led to the Direction of Many Academic Studies Towards Studying What The Principles and Determinants of Institutional governance raise in the environments of Educational Institutions, Which led to More Focus Interest in Institutional Governance, and The Study Problem Was Identified in Dealing With a Number of Administrative and Organizational Problems, and The Economic and Institutional Challenges Facing The Administration of Pre-University Education, and Answering The question: Can the Requirements for Developing The Pre-University education Administration Respond to The Principles and Determinants of Institutional Governance? The Aim of The Research is to Reach a Proposed Vision for The development of Pre-University Education Management Using Institutional Governance, and to Review Implementation Requirements, Obstacles and Mechanisms for overcoming Implementation Obstacles. The Research Used The Descriptive Approach and Collected Data Through Secondary Sources Such as Magazines, Books, Periodicals and Previous Studies, and The Use of the Comparative Approach, Which Enabled The Description of International Experiences and Lessons Learned, and to Identify The Similarities and Differences Between The Experiences of The Countries in Question, in Order to Develop a Proposed Vision for The Development of Pre-University Education Management Using Corporate Governance. The Research Concluded a Number of Results, Including: Lack of Awareness Among Stakeholders of The Concept, Frameworks and Dimensions of Institutional Governance, Weak Legislative and Regulatory Frameworks as a Result of The Conflict Between The Governing Regulations and Systems, and The Absence of Executive Procedures. The most important recommendations of the research: Establishing a Governance Department at all Administrative Levels Consisting of a Number of Committees, Responsible for Ensuring Accountability and Accountability, Preparing Reports and Internal and External Reviews, Nomination to Obtain a License to Practice The Teaching Profession, Following up on The Implementation of Policies and Programmes, Reviewing Incentives and Rewards Systems, and Reviewing The List of Disciplinary Sanctions.